The book of Qt 4 : the art of building Qt applications - Molkentin, Daniel (Open Source Press ; No Starch Press, 2007)
The Qt toolkit is widely used for the development of GUI applications as well as console tools and servers. Qt is most notably used in KDE (a free Linux desktop) the Opera web browser, Skype, and Google Earth.In The Book of Qt 4, Daniel Molkentin, a core developer of KDE, uses practical examples to explain Qt characteristics like the signal slot concept and its event system. He guides the reader through developing applications both with and without Qt's graphical GUI builder, ""Qt Designer."" Topics covered include tools needed to create dialog boxes, steps to follow when developing a GUI-base.